Long-run inflation expectations - Jonas D. M. Fisher; Leonardo Melosi; Sebastian Rast (Federal Reserve Bank of Chicago, 2025)
Professional forecasters' long-run inflation expectations overreact to news and exhibit persistent, predictable biases in forecast errors. A model incorporating overconfidence in private information and a persistent expectations bias-which generates persistent forecast errors across most forecasters-accounts for these two features of the data, offering a valuable tool for studying long-run inflation expectations. Our analysis highlights substantial, timevarying heterogeneity in forecasters' responses to public information, with sensitivity declining across all forecasters when monetary policy is constrained by the effective lower bound. The model provides a framework to evaluate whether policymakers' communicated inflation paths are consistent with anchored long-run expectations.
Keywords: E31; D83; E52; E37; 330; Panel survey data; long-run inflation expectations; rationality; expectation bias; overconfidence; overreaction; central bank communications; anchoring